2017
DOI: 10.1136/annrheumdis-2017-212127
|View full text |Cite
|
Sign up to set email alerts
|

Dual IL-17A and IL-17F neutralisation by bimekizumab in psoriatic arthritis: evidence from preclinical experiments and a randomised placebo-controlled clinical trial that IL-17F contributes to human chronic tissue inflammation

Abstract: ObjectiveInterleukin (IL)-17A has emerged as pivotal in driving tissue pathology in immune-mediated inflammatory diseases. The role of IL-17F, sharing 50% sequence homology and overlapping biological function, remains less clear. We hypothesised that IL-17F, together with IL-17A, contributes to chronic tissue inflammation, and that dual neutralisation may lead to more profound suppression of inflammation than inhibition of IL-17A alone.MethodsPreclinical experiments assessed the role of IL-17A and IL-17F in ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
199
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 198 publications
(229 citation statements)
references
References 30 publications
(20 reference statements)
7
199
0
9
Order By: Relevance
“…However, in the experimental colitis mouse model neutralization of both IL-17A and IL-17F ameliorated colitis, whereas neutralization of IL-17A or IL-17F alone had limited effect [19]. Of relevance, a recent report using human in vitro models suggest that dual blockade of IL-17A and IL-17F in Th17 supernatants was more effective at reducing the secretion of pro-inflammatory mediators from target cells than blockade of IL-17A alone [20]. Finally, early clinical studies with bimekizumab, a dual IL-17A and IL-17F neutralizing antibody, have shown rapid and profound clinical responses in psoriasis [21] and PsA [20] patients suggesting an unappreciated role for IL-17F in addition to IL-17A in promoting inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the experimental colitis mouse model neutralization of both IL-17A and IL-17F ameliorated colitis, whereas neutralization of IL-17A or IL-17F alone had limited effect [19]. Of relevance, a recent report using human in vitro models suggest that dual blockade of IL-17A and IL-17F in Th17 supernatants was more effective at reducing the secretion of pro-inflammatory mediators from target cells than blockade of IL-17A alone [20]. Finally, early clinical studies with bimekizumab, a dual IL-17A and IL-17F neutralizing antibody, have shown rapid and profound clinical responses in psoriasis [21] and PsA [20] patients suggesting an unappreciated role for IL-17F in addition to IL-17A in promoting inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of studies have identified the expression of IL-17F in RA and PsA synovial tissue when compared with osteoarthritis (OA) samples via immunohistochemistry analysis [14,25]. In addition, a recent study showed detectable levels of IL17F mRNA in six out of 14 PsA synovial tissue samples [20]. A different study, however, reported that while IL-17A protein was detected in the supernatant of stimulated RA synovial fluid mononuclear cells, no IL-17F protein was detectable [18].…”
Section: Introductionmentioning
confidence: 99%
“…Observations made by Wang et al (Glatt et al, ) indicate the presence of synergistic effects of IL‐17 and TNF on the intensity of the molecular basis of pigmentation changes observed in psoriasis. In addition, IL‐17 levels have been shown to be one of the factors determining the efficacy of anticytokine therapy (Berthuy, Blum, & Marquette, ; Codreanu et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Observations made by Wang et al (Glatt et al, 2018) determining the efficacy of anticytokine therapy (Berthuy, Blum, & Marquette, 2016;Codreanu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of bispecific antibodies are that they may be more selective, they may be efficacious at lower dosages, they may hit two or more pathways simultaneously, thus preventing escape mechanisms, and with specific modulation of their three-dimensional structure, pharmacokinetic properties of those antibodies may be intentionally determined. [26,27] An additional strategy could involve specific binding to certain tissues/ cells to result in a target organ specific enrichment of the antibody with higher local efficacy and less systemic side effect potential. [25] The most advanced example of a currently ongoing late-stage clinical development programme for a multi-specific targeting strategy is in Ph3 with bimekizumab targeting IL17A/F in psoriasis and psoriatic arthritis.…”
Section: The Need For Multicomponent Therapymentioning
confidence: 99%